Arthritis as the main or only symptom of hepatitis B infection. Issue 716 (June 1985) - Pease, C.; Keat, A.
Abstract : The clinical features of three patients who presented in different ways with inflammatory polyarthritis secondary to acute hepatitis B virus infection are discussed. The importance of early recognition of this condition is stressed.